Physical therapy management for muscle tightness in a surfing athlete: a case report study - Govinda Vittala; I Putu Prananda Dinata; Putu Devinda Ardaswari; Tabita Febyola Wijaya; Lanang Imam Herlambang; I Dewa Gede Alit Kamayoga (Physical Therapy Journal of Indonesia, 2024)
Background: Muscle tightness refers to the sensation of tension or stiffness in the muscles, often resulting from factors such as excessive physical activity, inadequate warm-up before exercise, muscle injury, or underlying medical conditions. This article describes a case of a surfer patient with muscle tightness who has had ACL reconstruction meniscectomy and physical therapy management. Case description: The patient was a 51-year-old male surfing athlete from New Zealand diagnosed with muscle tightness. The patient had a history of ACL and meniscus injuries, followed by ACL reconstruction and meniscectomy of the right knee. The patient was on vacation in Bali, and he was surfing every day. The patient underwent physical therapy twice a week. The intervention program included modalities (transcutaneous electrical nerve stimulation and ultrasound), manual therapy (massage and patellar mobilization), and exercise therapy (range of motion exercises, strength training, and stretching). Conclusion: The physical therapy intervention program designed for one week can yield positive results in reducing pain levels, improving the range of motion of the right knee, increasing the circumference of the right knee segment, and enhancing the functional activities of the right knee.